Releasing the Criminals: Polemics on The Provision of Assimilation Prisoners in The Covid-19 Pandemic Case - Sulistyowati, Widya Kurnia (The Indonesian Journal of International Clinical Legal Education, 2020)
COVID-19 is a contagious disease in humans caused by a new type of coronavirus found in December 2019. The method of transmission is relatively easy to do to prevent COVID-19 transmission, one that uses social and physical distance orders. In the jails, the capacity has exceeded the specified limit. Therefore, the existence of policies regarding social and physical distancing also causes the government to provide assimilation to prisoners in order to prevent the spread of COVID-19 and on humanitarian grounds. The provision of assimilation is specifically for prisoners with special crimes and is excluded for terrorism prisoners, narcotics inmates and corruption prisoners.